Histological transformations of fascia dentata of mice and rats in the first postnatal days - Llamilet Magdariaga Hernández; Marta de las Nieves Castro Bosch; Soini González Gámez (Centro Provincial de Información de Ciencias Médicas, 2018)
A descriptive, observational and cross-sectional study was carried out in 160 histological cuts of the hippocampus fascia dentata from mice BALB/c and rats white Wistar, in the Laboratory of Biomedical Investigations from Santiago de Cuba Medical University, from September, 2013 to the same month in 2014, with the aim of determining the histological transformations that take place in this fascia in the second and sixth posnatal days. The microscopic observation of these cuts was carried out using the software Image J. The extension of the fascia at the sixth day of life was larger in the mice; the maximum increases of thickness in both types of rodents were in the hilus, and the granular stratum was of smaller growth in rats. The celularity in the rodents presented larger proportions in the three regions from the hilus at the second day, but it decreased at the sixth day, while the areas related to the hilus maintained a greater quantity of cells; however, the cellular number diminished in both molecular regions of the rats fascia.